Mislabeling Seafood Does Not Promote Sustainability: A Comment on Stawitz et al. (2016). Issue 6 (27th February 2017) - Mariani, Stefano; Cawthorn, Donna‐Mareè; Hanner, Robert
Abstract: Recently, Stawitz et al . collated existing primary literature on DNA identification of finfish products and conducted a series of analyses to explore the environmental and economic ripples of species substitution. While we agree that the assessment of the impacts of seafood mislabeling is paramount, we show that the main conclusion of the study, which hints at a positive ecological impact arising from misnaming traded finfish species, is not warranted by the data, and may inadvertently cause damage to public perceptions of seafood provision, sustainability, and marine resource management.